DETERMINAN KESIAPSIAGAAN SISWA DALAM IMPLEMENTASI PENGURANGAN RISIKO BENCANA MELALUI PENDIDIKAN FORMAL DI SMAN UNGGUL SIGLI KECAMATAN PIDIE KABUPATEN PIDIE - Cut Wardah; Donal Nababan; Mido Ester. J. Sitorus; Elsarika Damanik (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Background: Indonesia is an archipelago and it is located between the Pacific Ocean and Indian Ocean. Geographically, it is located in a series of tectonic plates of Australia, the Eurasian Pacific and the Philippines, which makes Indonesia vulnerable to geographical changes. Due to those reasons, Indonesia becomes one of the countries that has areas prone to disasters including earthquakes and tsunamis.Purpose: This study aims to analyze the relationship between knowledge and attitude variables, emergency response plans, early warning systems, and mobility of resources on student preparedness in implementing disaster risk reduction through formal education at SMA Negeri Unggul Sigli, Pidie Regency in 2020. Method: This was an analytical study with a cross-sectional design. The population in this study were 140 of students at SMA Negeri Unggul Sigli by using Stratified Random Sampling, 104 of students consisting of 50 boys and 90 girls. This research was conducted from Oktober - December 2020. Univariate, bivariate and multivariate data analysis with Chi-square test and Logistic Regression test were used in this study. Results: Based on the results of the bivariate analysis with the Chi-square statistical test, there was a significant relationship between With variables; Knowledge and attitude with a p value of 0.022; Emergency response plan with p value of 0.002; Early warning system with p. value: in the amount of 0.000; and Resource mobility with p. value of 0.006. on student preparedness in implementing disaster risk reduction (pâ‰¤.0, 05). The results of multivariate analysis with multiple logistic regression tests obtained variables that had a significant effect on student preparedness in implementing disaster risk reduction (PRB), namely: the Resource mobility variable with a coefficient of B. 0,512 and Exp (B) of 5,99. This means that students who get an the resource mobility well have a greater chance of being ready to implement disaster risk reduction 5,99 than students who do not get an the Resource mobility properly. Conclusion: obtained variables that had a significant effect on student preparedness in implementing disaster risk reduction (PRB), namely: the Resource mobility variable.